Minisatellites: Mutability and Genome Architecture - Vergnaud, Gilles; Denoeud, France

(untitled) (Genome Research, 2000)
Minisatellites have been found in association with important features of human genome biology such as gene regulation, chromosomal fragile sites, and imprinting. Our knowledge of minisatellite biology has greatly increased in the past 10 years owing to the identification and careful analysis of human hypermutable minisatellites, experimental models in yeast, and recent in vitro studies of minisatellite recombination properties. In parallel, minisatellites have been put forward as potential biomarkers for the monitoring of genotoxic agents such as ionizing radiation. We summarize and discuss recent observations on minisatellites. In addition we take advantage of recent whole chromosome sequence data releases to provide a unifying view which may facilitate the annotation of tandem repeat sequences.